Pengembangan Flipbook Berbasis PBL Setting Flip Pdf Professional sebagai Media Pembelajaran pada Materi Sistem Reproduksi Kelas XI SMA - Dewi, Ni Putu Sri Ratna; Ni Made Pebriani Santika Dewi; Arnyana, Ida Bagus Putu (Jurnal Pendidikan Biologi Undiksha, 2022)
The purpose of this research is to find out (1) the specification of Flipbook with PBL setting in Reproductive system subject for student grade XI SMAN 1 Mengwi, (2) the validity of Flipbook media, and (3) the practicality of Flipbook media. This study uses the ADDIE development model which consists of 5 stages. There are the Analysis, Design, Development, Implementation, and Evaluation. The evaluation stage in this development research was not carried out due to research limitations. The location of this research is at SMAN 1 Mengwi. The validity test used Gregory's calculations that consist with 2 material experts, 2 media experts, and 2 Linguist experts. From the three groups of experts, the GVC (Gregory Validity Coefficient) value is 1 from the Material Expert, 1 from the Media, and 1 from the Linguist expert. So the result means the Flipbook is very feasible to be used in the learning process at SMAN 1 Mengwi. Practicality tests were conducted on 4 Biology teachers from SMAN 1 Mengwi and 12 students from SMAN 1 Mengwi who have different cognitive levels, ranging from high, medium, and low cognitive levels. From the combined value of practicality by teachers and students, the percentage value of practicality is 92.86%. This value indicates that the Flipbook of the Human Reproductive System for Senior High School is very practical to use in the learning process at SMAN 1 Mengwi.